2014
DOI: 10.1371/journal.pone.0092254
|View full text |Cite
|
Sign up to set email alerts
|

Snail Family Members Unequally Trigger EMT and Thereby Differ in Their Ability to Promote the Neoplastic Transformation of Mammary Epithelial Cells

Abstract: By fostering cell commitment to the epithelial-to-mesenchymal transition (EMT), SNAIL proteins endow cells with motility, thereby favoring the metastatic spread of tumor cells. Whether the phenotypic change additionally facilitates tumor initiation has never been addressed. Here we demonstrate that when a SNAIL protein is ectopically produced in non-transformed mammary epithelial cells, the cells are protected from anoikis and proliferate under low-adherence conditions: a hallmark of cancer cells. The three SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…It was reported that SNAI1 could induce EndMT under certain conditions [14,15,17,[39][40][41][42]. Besides, SNAI1 also had a role in embryonic vessel formation and in vitro angiogenesis [19,20].…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that SNAI1 could induce EndMT under certain conditions [14,15,17,[39][40][41][42]. Besides, SNAI1 also had a role in embryonic vessel formation and in vitro angiogenesis [19,20].…”
Section: Discussionmentioning
confidence: 97%
“…Infections were performed as described in [64]. Infected cells were selected with puromycin (1 μg/ml) before being plated in ultra-low adherent conditions or plated on soft agar.…”
Section: Methodsmentioning
confidence: 99%
“…Out of these five genes, ROR1, SNAI3, TET1, TSPAN13 were significantly upregulated in metastatic compared with primary ( Figure 5). Upregulation of ROR1 in melanoma was reported recently [34], while overexpression of TSPAN13 was reported in other cancers [35] and SNAI3 involved in the EMT process, however, its role in melanoma is not well documented yet [36]. Intriguingly, loss of 5-hydroxymethylcytosine and downregulation of TET1 in melanoma compared with nevi was reported as a key feature of melanoma [37].…”
Section: Mir-193bmentioning
confidence: 95%